New records of six moth (Lepidoptera: Erebidae, Lasiocampidae) species in south African countries, with comments on their distribution - Delabye, Sylvain; Sedláček, Ondřej; Maicher, Vincent; Tropek, Robert (Biodiversity data journal, 2020)
BACKGROUND: Southern Africa hosts a high diversity of ecosystems and habitats with a tremendous diversity of Lepidoptera. Although it is one of the most studied parts of the Afrotropics, the knowledge on diversity and distribution of south African moth fauna remains insufficient. To partly fill this gap, we surveyed macromoths by automatic light traps in five localities in two relatively less sampled south African countries. NEW INFORMATION: We reported six species and one genus (Remigioides) of moths which had not yet been recorded in Namibia or Zimbabwe. Although none of these records broadened the known distribution of individual species to a new biogeographical region, they still fill important gaps in their distributions. The known distributional ranges of two species have been substantially extended, although they are still within the same biogeographical regions: ca. 800 km southwards for Remigioides remigina (Mabille, 1884) and ca. 600 km westwards for Haplopacha cinerea Aurivillius, 1905.
Keywords: faunistic report; Afrotropics; savannahs; light trapping; southern African region; Zambezian region